The supply analysis of the accident insurance - Kříž, Jakub; Radová, Jarmila; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2011)
This bachelor thesis analyzes the offer of the accident insurance. Describes the history of the private accident insurance. Professionally defined the accident insurance, the insurance contract, the premiums and its amount. Defines the types of insurance and the exclusions in the indemnification. Then it also states the basic types of the accident insurance and its specific forms. The work focuses on the activities of the insurance intermediaries and their role in the offer of the accident insurance. Characterizes the current insurance market and the role the accident insurance plays in it. For the purposes of the detailed analysis are selected four insurance companies operating on the Czech market. After their performance follow the comparative examples, in which are indicated the differences in the amounts of annual premiums and amounts of indemnification. The concluding part presents the results of a questionnaire relating to accident insurance.
Vedoucí práce: Jarmila Radová
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2011
Rok obhajoby 2011
Keywords: bankovnictví a pojišťovnictví [obor bakal. práce]; bakalářské práce; bachelor's theses